Prototype Self-Adaptive Traffic Light Control System Using Cameras - Channareth Srun; Saran Meas; Sok Oeun Un; Saokun Khim; Virbora Ny (EPI International Journal of Engineering, 2021)
Cambodia is a developing country with rapid development. More vehicle usage on the road increased, this leads to more traffic problems. The traditional traffic light and traffic police officer help solve the problem at a level and limited conditions. For a better improvement, the smart traffic light is a good solution that can adapt to the real-world environment. There are four cameras are used to capture and analyze the vehicle traffic to control the modes of the traffic light. This method gives the improvement over the limited time of the traditional traffic light. This smart traffic light comes with three-term mode conditions including normal mode, camera mode, and night mode.